The Role Psychological Contract Plays in Organizational Behaviour: A Case Study of a Public University in Ghana - Agbozo, George Kafui; Ansa-Bonnah, Ellen; Hoedoafia, Mabel A.; Atakorah, Yaw Boateng (European Scientific Journal, ESJ, 2018)
This paper examined the role of psychological contract on organisational behaviour and organisational commitment. A case study approach of research design was adopted in gathering data from 65 respondents from a public university in Ghana. Stratified random sampling method was employed to group the respondents into strata. Purposive sampling method was then employed to select the respondents for the study. The field data was analysed both quantitatively and qualitatively. Results from the study showed that commitment between employer and employees depend on the fulfilment of the perceived expectations between the two parties. Again, the study pointed out that majority of the employees would leave the organisation if their perceived expectations were not met. The study recommended that aside the written conditions of contract, employees must behave appropriately so that they will get the best from management.